Описание двух новых видов кровососущих мокрецов рода Culicoides (Diptera, Ceratopogonidae) с Украины - Шевченко, А.К. (Вестник зоологии, 1972)
Two new species of Culicoides from the Ukraine are described. C. luganicus sp. n. is found in the Steppe zone of the Ukraine (vil. Stanitsa Luganskaya of the Voroshilovgrad region, May—June, 1964); C. atripennis sp. n. was found in mountainous regions of the Crimea (biting midges are reared from pupae caught in flood water basins of the river Chernaya, the Crimean reservation, July, 1971). The description is made with respect to males and females.